Development and research of the effectiveness of using an automated aquaponic system for home cultivation of microgreens - Chebotarev Daniil; Naumov Ivan (BIO Web of Conferences, 2024)
In this study, an automated system was developed for the home cultivation of microgreens using aquaponics technology using modern technologies and a review of literary sources. The researcher was convinced that the automation system of the aquafarm is able to significantly simplify human care of the aquarium. Experimentally, the advantage of using this system over the "classic" method of growing microgreens, in terms of the rate of ascent of the stems, was tested. It was also verified that the developed automated system for a home aquapon installation has a positive effect on the biological ecosystem. Monitoring of the main indicators of water quality has shown sufficient effectiveness of this method to neutralize indicators such as nitrates. In the future, this work can become the basis for conducting a large number of experiments for longer periods and monitoring a wide range of water quality indicators and growing large types of seeds.